2020
DOI: 10.1186/s12879-020-05180-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of meteorological factors on the incidence of mumps and models for prediction, China

Abstract: Background: Mumps is an acute respiratory infectious disease with obvious regional and seasonal differences. Exploring the impact of climate factors on the incidence of mumps and predicting its incidence trend on this basis could effectively control the outbreak and epidemic of mumps. Methods: Considering the great differences of climate in the vast territory of China, this study divided the Chinese mainland into seven regions according to the administrative planning criteria, data of Mumps were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…The results of the time series of notifiable respiratory infectious diseases indicated that the incidence of notifiable respiratory infectious diseases in Shandong Province has obvious seasonality, with peaking in winter and spring and a few notifiable respiratory infectious diseases in early summer, which may be related to climatic factors [ 25 28 ]. In addition, we found that the incidence of measles, tuberculosis and meningococcal meningitis showed a downward trend, and the incidence of influenza A (H1N1) and rubella showed sporadic and have an outbreak trend occasionally.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the time series of notifiable respiratory infectious diseases indicated that the incidence of notifiable respiratory infectious diseases in Shandong Province has obvious seasonality, with peaking in winter and spring and a few notifiable respiratory infectious diseases in early summer, which may be related to climatic factors [ 25 28 ]. In addition, we found that the incidence of measles, tuberculosis and meningococcal meningitis showed a downward trend, and the incidence of influenza A (H1N1) and rubella showed sporadic and have an outbreak trend occasionally.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the time series of respiratory infectious diseases indicated that the incidence of respiratory infectious diseases in Shandong Province has obvious seasonality, with peaking in winter and spring and a few respiratory infectious diseases in early summer, which may be related to climatic factors [26][27][28][29]. In addition, we found that the incidence of measles, tuberculosis and meningococcal meningitis showed a downward trend, and the incidence of in uenza A (H1N1) and rubella showed sporadic and have an outbreak trend occasionally.…”
Section: Discussionmentioning
confidence: 99%
“…A plenty of studies found that temperature had an effect on prevalence of mumps (Ho et al 2015;Onozuka and Hashizume 2011). A recent study from the western China indicated that precipitation and wind speed also had effect on the prevalence of mumps (Zha et al 2020). Warm and humid weather would promote MuV reproduction and evolution, enhancing the infection risk (Nenna et al 2017).…”
Section: Distributed Lag Non-linear Models (Dlnm)mentioning
confidence: 99%